Changes in depression in the immediate post-discharge phase in a cardiac rehabilitation population assessed by the Cardiac Depression Scale - Davidson, Patricia; Salamonson, Y.; Webster, J.; Andrew, S.; Digiacomo, Michelle; Gholizedah, L.; Newton, Phillip; Moser, D. (Lippincott Williams & Wilkins, 2008)
Introduction: Depression is increasingly a focus of attention in the management of heart disease. Clinicians in cardiac rehabilitation are well placed to assess and facilitate management of symptoms of depression, yet the timing and interpretation of measurements remains unclear.Methods: We administered the Hare-Davis Cardiac Depression Scale (CDS) in a usual care, outpatient cardiac rehabilitation (CR) program in a metropolitan setting. As part of routine assessment and monitoring of outcomes in a 6 week outpatient CR program, we administered the CDS at entry, completion of the six week program and at 12 months.Results: Data was available on 151 patients for the three measurement points. At baseline, the CDS was 76.07 (22.38), which dropped at 6 weeks to 62.85 (21.69) but increased slightly at 12 months to 69.79 ( 24.36). The change in these scores were statistically significant for all measurement points (P<0.03). The trend of change for the CDS was reflected in the subscale scores which dropped at 6 weeks but had increased slightly at 12 months.Discussion: Findings demonstrate a positive impact of CR on CDS scores at 6 weeks and 12 months, although there was a trend for increased scores at one year. This observation requires further investigation and underscores the importance of longitudinal studies.